Analisis dan Perancangan Sistem Informasi Manajemen Layanan Pelanggan pada PDAM Tirta Mayang Kota Jambi - Zulfikri Akbar; Herry Mulyono (LPPM Universitas Dinamika Bangsa, 2017)
Customer satisfaction towards PDAM Tirta Mayang Jambi services is associated with the level of servicequality of service provided. The use of IT can help to improve the quality of services at PDAM TirtaMayang Jambi and is viewed as a strategic asset that helps to determine business strategies of PDAMTirta Mayang Jambi. This research was conducted with the aim to design information system of PDAMTirta Mayang ITSM Jambi. Data collection method used is through interview, observation anddocumentation, as the data and information obtained were analyzed which resulted in an analysis of thecondition of the running system. The system is designed in the form of protitipe which its design followseach stage of ITIL version 3 area service operation, namely: the process of event management, incidentmanagement (incident identification, incident logging, incident categorization, incident prioritization,initial diagnosis, incident escalation, investigation and diagnosis, resolution and recovery, incidentclosure), request fulfillment, problem management, and access management. The results of this study is inthe form of an information system design ITSM on PDAM Tirta Mayang Jambi City designed basedframework ITIL version 3 service operation area.